Nectin-like proteins mediate axon–Schwann cell interactions along the internode and are essential for myelination - Maurel, Patrice (The Rockefeller University Press, 2007)
Axon–glial interactions are critical for the induction of myelination and the domain organization of myelinated fibers. Although molecular complexes that mediate these interactions in the nodal region are known, their counterparts along the internode are poorly defined. We report that neurons and Schwann cells express distinct sets of nectin-like (Necl) proteins: axons highly express Necl-1 and -2, whereas Schwann cells express Necl-4 and lower amounts of Necl-2. These proteins are strikingly localized to the internode, where Necl-1 and -2 on the axon are directly apposed by Necl-4 on the Schwann cell; all three proteins are also enriched at Schmidt-Lanterman incisures. Binding experiments demonstrate that the Necl proteins preferentially mediate heterophilic rather than homophilic interactions. In particular, Necl-1 on axons binds specifically to Necl-4 on Schwann cells. Knockdown of Necl-4 by short hairpin RNA inhibits Schwann cell differentiation and subsequent myelination in cocultures. These results demonstrate a key role for Necl-4 in initiating peripheral nervous system myelination and implicate the Necl proteins as mediators of axo–glial interactions along the internode.